Correlated Brownian Motions as an Approximation to Deterministic Mean-Field Dynamics - Kotelenez, P. (Український математичний журнал, 2005)
We analyze the transition from deterministic mean-field dynamics of several large particles and infinitely many small particles to a stochastic motion of the large particles. In this transition the small particles become the random medium for the large particles, and the motion of the large particles becomes stochastic. Under the assumption that the empirical velocity distribution of the small particles is governed by a probability density F, the mean-field force can be represented as the negative gradient of a scaled version of F. The stochastic motion is described by a system of stochastic ordinary differential equations driven by Gaussian space-time white noise and the mean-field force as a shift-invariant integral kernel. The scaling preserves a small parameter in the transition, the so-called correlation length. In this set-up, the separate motion of each particle is a classical Brownian motion (Wiener process), but the joint motion is correlated through the mean-field force and the noise. Therefore, it is not Gaussian. The motion of two particles is analyzed in detail and a diffusion equation is deduced for the difference in the positions of the two particles. The diffusion coefficient in the latter equation is spatially dependent, which allows us to determine regions of attraction and repulsion of the two particles by computing the probability fluxes. The result is consistent with observations in the applied sciences, namely that Brownian particles get attracted to one another if the distance between them is smaller than a critical small parameter. In our case, this parameter is shown to be proportional to the aforementioned correlation length. Проаналізовано перехід від детерміністської динаміки середнього поля декількох великих частинок та нескінченної кількості малих частинок до стохастичного руху великих частинок. Під час цього переходу маленькі частинки перетворюються у випадкове середовище для великих частинок, а рух великих частинок стає стохастичним. Якщо припустити, що розподіл емпіричної швидкості малих частинок визначається щільністю розподілу F, то силу середнього поля можна подати як від'ємний градієнт масштабного перетворення F. Стохастичний рух описано системою стохастичних звичайних диференціальних рівнянь, керованих гауссовим просторово-часовим білим шумом та силою середнього поля як інтегральним ядром, інваріантним відносно зсуву. Масштабування зберігає малий параметр при переході (так звану довжину кореляції). У даній постановці окремий рух кожної частинки є класичним броунівським рухом (вінерівським процесом), але спільний рух корелюється силою середнього поля і шумом. Тому він не є гауссівським. Детально проаналізовано рух двох частинок і виведено рівняння дифузії для різниці положень двох частинок. Коефіцієнт дифузії в останньому рівнянні є просторово залежним, що дозволяє визначити області притягання та відштовхування двох частинок шляхом розрахунку течій імовірностей. Результат узгоджується із спостереженнями у прикладних науках, а саме, з фактом, що броунівські частинки притягуються одна до одної, якщо відстань між ними менша за критичний малий параметр. У випадку, що вивчається, показано, що цей параметр пропорціональний згаданій вище довжині кореляції.